2021
DOI: 10.20870/oeno-one.2021.55.4.4795
|View full text |Cite
|
Sign up to set email alerts
|

Is foliar Cl- concentration the cause of photosynthetic decline in grapevine during mild salinity?

Abstract: Moderate levels of Cl- have been associated with grapevine salt tolerance. The hypothesis to be tested in this work is: photosynthesis in grapevine is negatively correlated with foliar Cl- concentration. To further test this hypothesis, multiple mild salinity experiments on four different Vitis genotypes (Cabernet-Sauvignon, Riparia Gloire, Ramsey and SC2) were conducted and photosynthesis, ion concentrations and gene expression responses were quantified. The salt-tolerant rootstock Ramsey had greater Cl- excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The generalized reduction found in net photosynthesis (A N ) under saline conditions, regardless of the rootstock ( Figure 2 ), is related to stomatal and mesophyll conductance limitation, as there were no major differences in WUE i beyond those expected, given the differences in water status ( Flexas et al, 2004 ). Reductions are in line with those found by Flexas et al (1999) in ‘Tempranillo’ and Baeza et al (2007) and Baggett et al (2021) in ‘Cabernet-Sauvignon’ cultivars. Moreover, no differences were detected in the ratio of internal to atmospheric CO 2 concentration (Ci/Ca) between treatments (0.76 and 0.75 in Control and Saline treatments, respectively; data not shown).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The generalized reduction found in net photosynthesis (A N ) under saline conditions, regardless of the rootstock ( Figure 2 ), is related to stomatal and mesophyll conductance limitation, as there were no major differences in WUE i beyond those expected, given the differences in water status ( Flexas et al, 2004 ). Reductions are in line with those found by Flexas et al (1999) in ‘Tempranillo’ and Baeza et al (2007) and Baggett et al (2021) in ‘Cabernet-Sauvignon’ cultivars. Moreover, no differences were detected in the ratio of internal to atmospheric CO 2 concentration (Ci/Ca) between treatments (0.76 and 0.75 in Control and Saline treatments, respectively; data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…This genotype-dependent, though fuzzy, transcriptomic effects agree with our GSEA results, which identified much less statistically significantly (FDR q < 0.25) differentially expressed bins due to WQ in ‘Tempranillo’ grafted onto 1103P as compared to M4 and M1 ( Figure 3 ). Baggett et al (2021) , also similarly observed that salinity affected transcript abundance more in salt-sensitive genotypes than in salt-tolerant ones. Importantly, the leaf Cl – concentrations in our trial are higher than the ones reported by Urdanoz and Aragüés (2009) and Baggett et al (2021) , even though in the range of the ones found in ‘Cabernet Sauvignon’ onto 1103P by Dag et al (2015) using similar WQ.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Under the same saline concentration, 50 mM NaCl, Henderson et al [ 60 ] concluded that the salt-exclusion mechanisms in 140 Ruggeri (a close relative to R110 from the same parental background, but featuring higher salt tolerance) were not induced by salinity but, rather, seem to remain constitutively expressed, which could a similar case for R110. Similarly, constitutive gene expression profile was also shown in salt-tolerant variety Ramsey ( Vitis champinii ) against a saline treatment of 25 mM NaCl [ 63 ]. Given AS1B’s higher survival capability under salt stress, its responsive strategy could be an additional alternative to consider, in addition to known strategies in rootstocks showing constitutive expression.…”
Section: Discussionmentioning
confidence: 99%